Proceedings of the 2014 Conference on Interaction Design and Children 2014
DOI: 10.1145/2593968.2610482
|View full text |Cite
|
Sign up to set email alerts
|

3D printed tactile picture books for children with visual impairments

Abstract: Young children with visual impairments greatly benefit from tactile graphics (illustrations, images, puzzles, objects) during their learning processes. In this paper we present insight about using a 3D printed tactile picture book as a design probe. This has allowed us to identify and engage stakeholders in our research on improving the technical and human processes required for creating 3D printed tactile pictures, and cultivate a community of practice around these processes. We also contribute insight about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 4 publications
1
22
0
2
Order By: Relevance
“…We see evidence of this particularly in the emerging movements concerned with the development of inexpensive prosthetics and orthotics (Dombroski, Balsdon, & Froats, 2014;Koutny, Palousek, Koutecky, Zatocilova, Rosicky, & Janda, 2012;Record, Ratto, Ratelle, Ieraci, & Czegledy, 2013). Also evident of this movement is a recent project concerned with the low-cost printing of tactile books to support emerging literacy for children with low vision (Stangl, Kim, & Yeh, 2014). Academics in the fields of computer science and engineering are well positioned to take advantage of these technological advances and serve as bridges to community members (since the technologies are not entirely mainstream at this point).…”
Section: Democratization Of Designmentioning
confidence: 96%
“…We see evidence of this particularly in the emerging movements concerned with the development of inexpensive prosthetics and orthotics (Dombroski, Balsdon, & Froats, 2014;Koutny, Palousek, Koutecky, Zatocilova, Rosicky, & Janda, 2012;Record, Ratto, Ratelle, Ieraci, & Czegledy, 2013). Also evident of this movement is a recent project concerned with the low-cost printing of tactile books to support emerging literacy for children with low vision (Stangl, Kim, & Yeh, 2014). Academics in the fields of computer science and engineering are well positioned to take advantage of these technological advances and serve as bridges to community members (since the technologies are not entirely mainstream at this point).…”
Section: Democratization Of Designmentioning
confidence: 96%
“…Finally, follow-up studies are a way to also consider the ethics of taking away technologies that appear to be a real help for the user and which the user has come to depend on in everyday life. A lot of work within IDC and HCI in general focuses on evaluating assistive technologies and reporting results from these studies (e.g., [11,25]). However, what happens when this technology is taken away?…”
Section: The Value Of Follow-up Studiesmentioning
confidence: 99%
“…Researchers within the IDC community have for some years explored the potential of using technology to assist children with a variety of conditions (e.g., [11,25]). However, to date only limited research has focused on children with attention deficit hyperactivity disorder (ADHD), although ADHD is the most prevalent reported mental health diagnosis for children and teens [17], with a worldwide prevalence of approximately 5% [18].…”
Section: Introductionmentioning
confidence: 99%
“…2 Adapted Teaching Materials: "Do-It-Yourself" (DIY) With the emergence of 3D printing, new teaching tools are easy to make, such as 3D printed maps [3] or physical representations of graphics adapted for children with visual impairment [4]. Many recent studies have shown that 3D printing really enhances the creation of adapted materials such as globes for geography or biology lessons, geometric shapes for mathematics lessons, or different forms of plankton for biology lessons [5], but also 3D printed tactile books [6], or accessible museum exhibits [7]. Importantly, it has been shown that these materials improve understanding and satisfaction [8], but also engagement of students in Science, Technology, Engineering, and Mathematics [9].…”
Section: Introductionmentioning
confidence: 99%